Campbell Essential Biology With Physiology - Eric J. Simon (Pearson, 2015)
This best-selling textbook, known for its scientific accuracy, clear explanations, and intuitive illustrations, has been revised to further emphasize the relevance of biology to everyday life, using memorable analogies, real-world examples, conversational language, engaging new Why Biology Matters photo essays, and more.